Pathways into the Jungian world : phenomenology and analytical psychology - Brooke, Roger, 1953- (Routledge, 2000)
In Pathways into the Jungian World contributors from the disciplines of medicine, psychology and philosophy look at the central issues of commonality and difference between phenomenology and analytical psychology.